ChemInform Abstract: NMR in Organic Chemistry. Issue 17 (4th April 2013) - Courtieu, Jacques; Giraud, Nicolas; Lafon, Olivier; Lesot, Philippe; Lorthioir, Cedric; Nuzillard, Jean‐Marc
Abstract Review: 19 refs.